Investment booms, diverging competitiveness and wage growth within a monetary union: An AB-SFC model - Bernhard Schütz (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2022)
This paper proposes a 2-country stock-flow consistent agent-based model of a monetary union and exposes it to three supposed drivers of imbalances in the build-up to the Great Recession: unequal developments in investment, competitiveness and wages. The model has some innovative features: It does not rely on given propensities to import, with agents from different regions instead all being part of the same market and import shares emerging endogenously as a result of the geographical distance between agents. The model also features labor hoarding by firms and a banking sector that bears some Minskyan features. The model is able to replicate the low unemployment rates in the North that were paralleled with falling unemployment rates in the South together with trade imbalances in favor of the North.
Keywords: E12; E20; F45; 330; stock-flow consistent agent-based modeling; monetary union; international imbalances; investment; productivity; wages